ETHICAL AWARENESS AND FAIRNESS IN LANGUAGE TESTING - Bérešová, Jana (European Scientific Journal, ESJ, 2014)
The submitted paper outlines the impact of political decisions on language testing, predominantly on test scores of the tested population, test design and item-writing. Results from research referring to the comparison of test-takers´ performances in the years 2011-2013 reveal a necessity to be sensitive and aware of ethics and fairness in language testing. The research is focused on the professional decision of test developers, item writers and administrators to avoid negative impact and maximize positive washback. The paper focuses on the construct which underlies the B2 English test to provide information about abilities that the test is designed to measure. Testing grammar and vocabulary was supported by using multiple linear regression analysis. The new conditions for test takers in 2012 are analyzed and evaluated in three areas the number of the students applying for tests in English B2, the total scores of students and their grouped distributions and the scores achieved in productive skills and language in use. We conclude by examining the ethical implications of the new conditions for test takers and by demonstrating the effect the ethical dimension had on item writers in their design of subsequent tests. Fairness plays an important yet hard to implement role in test design, and it is often up to the administrators and test designers to cope with external obstacles in promoting this.